New Anthocyanidin and Anthocyanin Pigments from Blue Plumbago - Skaar, Irene; Jordheim, Monica; Byamukama, Robert; Mbabazi, Angella; Wubshet, Sileshi G.; Kiremire, Bernard; Andersen, Øyvind M. (Journal of agricultural and food chemistry, 2012)
Phytochemical investigations of blue plumbago (Plumbago auriculata Poir. syn. Plumbago capensis Thunb.) flowers have led to the isolation of six new anthocyanins based on three new anthocyanidins with 5,7-dimethoxylated A-rings. Their structures were identified by 2D nuclear magnetic resonance and high-resolution mass spectrometry as the 3-O-β- galactopyranosides (1,2,4) and 3-O-α-rhamnopyranosides (3,5,6) of 5,7-dimethyldelphinidin, 5,7-dimethylpetunidin, and 5,7- dimethylmalvidin. Identification of 1−6 implies new structures for the previously reported anthocyanidins pulchellidin, europinidin, and capensinidin to be 5,7-dimethoxy-3,3′,4′,5′-tetrahydroxyflavylium, 5,7,3′-trimethoxy-3,4′,5′-trihydroxyflavylium, and 5,7,3′,5′-tetramethoxy-3,4′-dihydroxyflavylium cations, respectively. The anthocyanins (0.4 mg/g flowers) were accompanied by the dihydroflavonol taxifolin 3′-O-β-glucopyranoside (1.4 mg/g) and the flavonols 5-methylquercetin 3-O-α-rhamnopyranoside (8.8 mg/g) and 5-methylquercetin (0.4 mg/g). The anthocyanins 1−6 are the first reported natural anthocyanins with no free hydroxyl groups in their 5- and 7-positions on their A-rings. They have thus no possibility of forming the tautomeric quinonoidal bases (anhydrobases), which are related to the free hydroxyl groups in the 5- and 7-positions of previously reported anthocyanins. The genes behind the 5,7-dimethoxylated anthocyanins might be useful for making anthocyanins with special properties (colors, etc.).
Keywords: Plumbago auriculata syn; Capensis; 7-dimethoxylated anthocyanidin A-rings; Capensinidin; Europinidin; Pulchellidin